Effects of different emulsifiers on tempering of dark chocolates - Chire, Gabriela C. (2010)
Effects of different emulsifiers, Soy lecithin as a controller and Polyglycerol polyricinoleate (PGPR) at 0,1 and 0,3% on a tempering method of dark chocolates was experimentally studied. The samples were prepared in the lab under the same conditions using a tempering method, the cooling curve represent the effect of the addition of a emulsifier about chocolate tempering behavior. The results show us certain emulsifiers of a PGPR group at 0,1% that conduct a better degree of temper of dark chocolates due to form good cooling curve with a zero slope during 2 minutes between 23,8 to 24,2 °C, where latent heat was off, finally the chocolate were solidificated, storaged and evaluated with respect to standard soy lecithin using in a chocolate production laboratory.